(untitled) (CAHIERS MAGELLANES-NS, 2024)
India's economy has been growing for the past few decades, which has led to general reductions in poverty; yet, poverty continues to be a significant problem. Being in a state of poverty means that a person does not have sufficient income or material things to meet their fundamental need. It's possible that social, economic, and political factors all play a role in poverty. There is a well-established connection between poverty and the underrepresentation of women in society. Within the scope of this study, the researcher concentrated on the general situation of poverty in the state of Assam, with a particular emphasis on the situation of rural women in the region. Assam economic surveys, human development reports, periodic labor force surveys, and a variety of credible papers and websites are the primary sources that were utilized for the current study. The findings of the research indicate that Not only is poverty pervasive in the districts of Assam, but it is also prevalent in both the rural and urban sections of the state. Women in rural areas are more susceptible to the effects of gender inequality than women in urban areas, despite the fact that gender inequality is ubiquitous in society in both urban and rural areas.